2009
DOI: 10.1111/j.1399-0012.2008.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

MELD and other predictors of survival after liver transplantation

Abstract: Severe pre-transplant liver disease, age > or = 65, non-white skin donor, and hepatocellular carcinoma are associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 37 publications
2
41
2
Order By: Relevance
“…Based on easily measurable laboratory data 2,5,6 , the MELD score has been considered more transparent and objective 2,5,7 for the ordination of liver disease on the waiting list for TH. Nevertheless, although it has been validated as a predictor of mortality in the list, the role of this scoring system for predicting survival after HT remains controversial 3,6,8 , which could suggest the need to readjust the graft allocation criteria for a model that also took into consideration the results of TH 8 . The objective of this study was to evaluate the accuracy of preoperative MELD score to predict survival after TH and also analyze factors predictive of mediumterm survival (24 months).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on easily measurable laboratory data 2,5,6 , the MELD score has been considered more transparent and objective 2,5,7 for the ordination of liver disease on the waiting list for TH. Nevertheless, although it has been validated as a predictor of mortality in the list, the role of this scoring system for predicting survival after HT remains controversial 3,6,8 , which could suggest the need to readjust the graft allocation criteria for a model that also took into consideration the results of TH 8 . The objective of this study was to evaluate the accuracy of preoperative MELD score to predict survival after TH and also analyze factors predictive of mediumterm survival (24 months).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…However, the shortage of liver grafts persists as the main limiting factor for its development 1 . In order to reduce the number of deaths on the waiting list 2,3 and eliminate possible confounding factors related to the chronological system, a new policy for allocation of liver grafts, based on the MELD (Model for End-Stage Liver Disease) system has been adopted in Brazil since July 4, 2006 4 . Based on easily measurable laboratory data 2,5,6 , the MELD score has been considered more transparent and objective 2,5,7 for the ordination of liver disease on the waiting list for TH.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…There are few studies correlating pretransplant MELD score with survival after living donor liver transplantation (6,20,33,35) . Hayashi et al (20) found no association between MELD score and patient survival in living donor liver transplantation recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated 78 consecutive patients submitted to living donor liver transplantation divided into two groups according to graft survival. Statistical analysis demonstrated the importance of MELD score and GRBW ratio for the prediction of post-transplant outcomes (5,6,27,31,36) . An increase in survival and improved outcomes of living donor liver transplantation were obtained in different series conducted in Europe and the United States when rigorous selection criteria were applied to donors and recipients (9,26,28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation